SEXUAL DIMORPHISM OF VARIOUS HAND DIMENSIONS AND ITS ROLE IN ESTIMATION OF STATURE AMONG BENGALI POPULATION– A PROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2025)
Introduction: Identification of unknown persons is one of the most important steps in forensic investigation. Gender fixation and stature estimation are two important parameters of identification. Sometimes challenging situations arise when medicolegal experts have to give opinion regarding sex and stature from mutilated body parts. Objective: The present study has been conducted to measure various dimensions of hand like hand length, palm length, middle finger length and breadth of hand, to search for sexual dimorphism of these dimensions, to estimate statute in both sexes using the above-mentioned dimensions and to formulate regression equation. Methodology: The study was performed in Rampurhat Govt. Medical College and Hospital from August 2023 to January 2024 on 584 subjects (384 males and 200 females). Data were collected using slide calliper, put into Microsoft excel office and statistically analysed. Result: We found mean value of all the dimension are more in males than in females. We calculated hand index and hand finger index. While hand index is more in males.
Keywords: Identification; Stature; Sexual dimorphism; Mutilated; Forensic